PENGARUH EKSPOR HASIL MINYAK DAN IMPOR MINYAK BUMI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Fadila Arza; Murtala Murtala (LPPM Universitas Malikussaleh – Indonesia, 2021)
This study aims to analyze the effect of oil product exports and petroleum imports on the economic growth of Indonesia. This study uses secondary data. The method used to analyze the relationship between endogenous and exogenous variables is a dynamic model with the Vector Error Correction Model (VECM) approach. The results in the long-term and short-term show that Oil Products Exports have a positive effect on the Economic Growth of Indonesia. In the long-term and short-term, petroleum imports negatively influence the economic growth of Indonesia.Keywords:Oil Product Exports, Crude Oil Imports, Economic Growth